Multidrug-resistant tuberculosis patients expressing the HLA-DRB1*04 allele, and after treatment they show a low frequency of HLA-II+ monocytes and a chronic systemic inflammation. (April 2021) - Ocaña-Guzman, Ranferi; Tellez-Navarrete, Norma A.; Preciado-Garcia, Mario; Ponce-Gallegos, Marco Antonio; Buendia-Roldan, Ivette; Falfán-Valencia, Ramcés; Chavez-Galan, Leslie
Abstract: Tuberculosis (TB) is an infectious disease caused by the bacilli Mycobacterium tuberculosis (Mtb); most TB patients are infected with strains of Mtb sensitive to first-line drugs (DS-TB), but in the last years has been increased the presence of multidrug-resistant TB (MDR-TB). HLA class II (HLA-II) is expressed on antigen-presenting cells and reported the association between HLA alleles and DS-TB in the Mexican population. We studied HLA-II + CD16 + monocytes frequency and its relation with a pro-inflammatory profile during DS-TB versus MDR-TB, both before as in response to anti-tuberculosis treatment. Peripheral blood was obtained from MDR-TB at the basal time (before use of therapy), 1, 3, and 8 months of anti-TB therapy (moTBt), whereas DS-TB at basal and 1 and 6 moTBt. Our data showed that contrary to DS-TB, MDR-TB patients have decreased the frequency of HLA-II + monocytes and increased the pro-inflammatory CD16 + monocytes from basal time until 8 moTBt. Similarly, only MDR-TB patients still have a high plasma level of IFN-γ and TNF pro-inflammatory cytokines for a long-time, and although MDR-TB patients showed an increased level of the soluble form of TIM3 and GAL9 at baseline, those molecules decreased as a response to anti-TB therapy. Finally, our data indicated that MDR-TB displayed DRB1*04 allele, suggesting an association between the infection by multidrug-resistance Mtb strain and the presence of the DRB1*04 allele in Mexican TB patients. Highlights: MDR-TB patients have decreased the frequency of HLA-II+ and increased CD16 + monocytes. MDR-TB patients maintain high plasma level of IFN-γ and TNF for a long-time. MDR-TB patients display DRB1*04 allele.